2007
DOI: 10.1108/02656710710720303
|View full text |Cite
|
Sign up to set email alerts
|

Developing zones of tolerance for managing passenger rail service quality

Abstract: Purpose -The purpose of this article is to develop and empirically test an extension to the three-column format SERVQUAL instrument to evaluate passenger rail service quality. Design/methodology/approach -This article combines the literatures of service quality and rail transport quality to develop the conceptual framework. Three new transport dimensions (comfort, connection, and convenience) are added to the original five SERVQUAL dimensions (assurance, empathy, reliability, responsiveness, and tangibles). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 33 publications
2
105
0
12
Order By: Relevance
“…Our findings correspond to the study of Cavana, Corbett, and Lo (2007), in which connectivity was established as an important factor affecting passenger perception of service quality.…”
Section: Results Of Exploratory Factor Analysissupporting
confidence: 51%
See 1 more Smart Citation
“…Our findings correspond to the study of Cavana, Corbett, and Lo (2007), in which connectivity was established as an important factor affecting passenger perception of service quality.…”
Section: Results Of Exploratory Factor Analysissupporting
confidence: 51%
“…Appropriate and timely information is what passengers expect from railways, and information emerged as an important predictor of passenger satisfaction in earlier studies (e.g., Cavana, Corbett, and Lo 2007;Rahman and Rahman 2009;Geetika and Nandan 2010;Swami and Parida 2015).…”
Section: Results Of Exploratory Factor Analysismentioning
confidence: 99%
“…That is why recent years have seen the development of derived importance methods based on CSS (Weinstein, 2000;Cavana et al, 2007;Pakdil and Aydin, 2007;Eboli and Mazzulla, 2007;Joewono and Kubota, 2007;Dell'Olio et al, 2010;Nurul--Habib et al, 2011;Jen et al, 2011) and from stated preference surveys (Hensher and Prioni, 2002;Hensher et al, 2003;Eboli and Mazzulla, 2008a;2008b;Dell'Olio et al, 2011;Cirillo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In their study looking at New Zealand, Cavana et al (2007) found assurance to be the most important service quality factor followed by responsiveness and empathy. In Malaysia, majority of the passengers of public transport indicated that they still have doubts over the safety assurance level provided by public transportations (Dahalan, D'Silva, Abdullah, Ismail & Ahmad, 2015).…”
Section: Assurancementioning
confidence: 99%
“…De Ona, De Ona, Eboli, & Mazzulla, 2015;Cavana, Corbett, & Lo, 2007;Prasad & Shekhar, 2010;Irfan, Kee, & Shahbaz, 2012). Some researchers (Brons, Givoni, & Rietveld, 2009;Rahaman & Rahaman, 2009;Geetika & Shefali, 2010;Chou, Kim, Kuo, & Ou, 2011;Eboli & Mazzulla, 2012) also focussed on examining the relationship between service quality and customer satisfaction.…”
Section: Age Segmentation For Predicting Behavioural Intention Of Usimentioning
confidence: 99%